BIOMECHANICAL PROPERTIES OF SMALL CORONARY ARTERIOLES IN VITAMIN D DEFFICIENCY AND PCOS: INTRODUCTION OF A NEW FEMALE RAT MODEL. (June 2018) - Hadjadj, L.; Horvath, E.; Sziva, R.; Monori-Kiss, A.; Pal, E.; Novak, A.; Nadasy, G.; Varbiro, S.
Abstract : Objective: PCOS and vitamin D deficiency are both frequent multifactorial endocrine disorders, lead to metabolic and early cardiovascular complications. According to actual data, there are an estimated 10.5 million fertile women suffering from PCOS only in the US. With this study we would like to describe the biomechanical changes of small coronary arterioles leading to a higher risk of cardial and cerebral insult. Design and method: 46 adolescent (21–28 day-old), 90–110 gramm-weighed female Wistar rats were grouped randomly in 4 groups: 24 animals recieved vitamin D supplemented diet, from which 12 animals went under transdermal testosterone treatment. 22 animals recieved vitamin D deficient diet, from which 11 were treated with testosterone. After 8 weeks of treatment, arterioles (in vivo diameter of 100–200 micrometer) from left anterior coronary artery were obtained. Isolated coronary arterioles were examined, in vitro, with pressure miography method. With videomicroscopic angiometry the inner and outer radii of the arteriole was evaluated. Such biomechanical properties as normal myogenic, maximal passive vasorelaxative and vasoconstrictive tone of the arterioles were obtained and statistically analysed. Results: In coronary arterioles, actual vitamin D status with and without testosterone supplementation caused significant differences in the vessel's maximal smooth muscle relaxant potential, tromboxane induced contraction capacity and normal myogenic tone. Conclusions: The novel finding of our study was, that the vitamin D deficency could lead to eutrophic remodelling and myogenic adaptation failure, which can elevate the risk of cardiovascular events. Supplementation of vitamin D could improve myogenic tone and relaxation, which hold cardiovascular benefits.